Characteristics and Qualities that Counselors Must Have - Feni Listari; Mudjiran; Yeni Karneli (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The personal characteristics of a competent counselor can help build a strong therapeutic relationship between the counselor and client, which is a key factor in achieving positive counseling outcomes. Counselors who have good personal qualities can create a safe, open and empathetic environment for clients, so that they feel heard, understood and supported. The method used is literature study, namely collecting data or information from various sources, including books, articles and other sources that are relevant to the topic or problem being researched. The conclusion of this research is that the personal characteristics of a good counselor are the key to creating a supportive environment, understanding clients' individual needs, and encouraging positive change. Counselors who possess these characteristics can provide effective and impactful counseling helping clients achieve their goals and improve their overall well-being.